PENGGUNAAN ASAP CAIR DARI TANDAN KOSONG KELAPA SAWIT (TKKS) DALAM PENEKANAN PERKEMBANGAN JAMUR SCHIZOPYLLUM COMMUNE (The use of liquid smoke from empty fruit stalks of oil palm in suppressing the fungus-growth of Schizophyllum commune Fries) - H.A. Oramahi Farah Diba, Gusti Eva Tavita, Reny Wahyuni (Tengkawang : Jurnal Ilmu Kehutanan, 2011)
The aim of this research was to evaluate the activity of liquid smoke from empty fruit stalks of oil palm to the Schizophyllum commune Fries fungus. Research was conducted in several steps, i.e. pyrolisis of liquid smoke and efficacy test of liquid smoke as antifungal. Agar media used was PDA (potatoes dextrose agar). Concentration of liquid smoke used for the treatment were 0; 0.25%; 0.50%; 0.75%; 1.00%; 1.25%; and 1.50% (v/v). The results indicated that the liquid smoke inhibited the Schizophyllum commune fungi growth. Concentration of liquid smoke resulted in significantly different antifungal activities. Liquid smoke with a concentration of 1% resulted in an average value of antifungal activity of 95.12%. The contents of organic fractions of liquid smoke, such as acid and phenol might be responsible for these antifungal activities. Keywords : liquid smoke, oil palm, empty fruit stalks, antifungal activity, Schizophyllum commune